2005
DOI: 10.1038/ng1678
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SIL1 cause Marinesco-Sjögren syndrome, a cerebellar ataxia with cataract and myopathy

Abstract: SIL1 (also called BAP) acts as a nucleotide exchange factor for the Hsp70 chaperone BiP (also called GRP78), which is a key regulator of the main functions of the endoplasmic reticulum. We found nine distinct mutations that would disrupt the SIL1 protein in individuals with Marinesco-Sjögren syndrome, an autosomal recessive cerebellar ataxia complicated by cataracts, developmental delay and myopathy. Identification of SIL1 mutations implicates Marinesco-Sjögren syndrome as a disease of endoplasmic reticulum dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
193
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(212 citation statements)
references
References 12 publications
10
193
0
5
Order By: Relevance
“…Thus, the loss of SIL1 protein function results in BiP recycling and the accumulation of unfolded proteins in the endoplasmic reticulum. [11][12][13] Senderek et al 5 were unable to identify any SIL1 gene mutations in four individuals with typical MSS. These reports suggested genetic heterogeneity in MSS or that individuals exhibiting MSS may contain mutations that are difficult to detect.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, the loss of SIL1 protein function results in BiP recycling and the accumulation of unfolded proteins in the endoplasmic reticulum. [11][12][13] Senderek et al 5 were unable to identify any SIL1 gene mutations in four individuals with typical MSS. These reports suggested genetic heterogeneity in MSS or that individuals exhibiting MSS may contain mutations that are difficult to detect.…”
Section: Discussionmentioning
confidence: 97%
“…The mutation we found was located in exon 6, which encodes the BiP-interacting domain. 5 Zhao et al 11 have reported that the SIL1 protein associates with the BiP chaperone to aid unfolded proteins in folding normally, and to help in the release of folded proteins. Thus, the loss of SIL1 protein function results in BiP recycling and the accumulation of unfolded proteins in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional reported eye findings include optic atrophy, glaucoma, microphthalmia, and retinal degeneration. 19 Congenital cataract-facial dysmorphism-neuropathy (CCFDN) syndrome is an autosomal recessive syndrome Figure 5 Dense nuclear sclerosis and posterior lenticonus in a CS2 patient. Congenital cataracts and microcephaly R Goyal et al described to date only in Vlax Roma gypsies.…”
Section: Discussionmentioning
confidence: 99%